The transformation of radiation oncology using real-time magnetic resonance guidance: A review. (November 2019) - Hall, William A.; Paulson, Eric S.; van der Heide, Uulke A.; Fuller, Clifton D.; Raaymakers, B.W.; Lagendijk, Jan J.W.; Li, X. Allen; Jaffray, David A.; Dawson, Laura A.; Erickson, Beth; Verheij, Marcel; Harrington, Kevin J.; et al.
Abstract: Radiation therapy (RT) is an essential component of effective cancer care and is used across nearly all cancer types. The delivery of RT is becoming more precise through rapid advances in both computing and imaging. The direct integration of magnetic resonance imaging (MRI) with linear accelerators represents an exciting development with the potential to dramatically impact cancer research and treatment. These impacts extend beyond improved imaging and dose deposition. Real-time MRI-guided RT is actively transforming the work flows and capabilities of virtually every aspect of RT. It has the opportunity to change entirely the delivery methods and response assessments of numerous malignancies. This review intends to approach the topic of MRI-based RT guidance from a vendor neutral and international perspective. It also aims to provide an introduction to this topic targeted towards oncologists without a speciality focus in RT. Speciality implications, areas for physician education and research opportunities are identified as they are associated with MRI-guided RT. The uniquely disruptive implications of MRI-guided RT are discussed and placed in context. We further aim to describe and outline important future changes to the speciality of radiation oncology that will occur with MRI-guided RT. The impacts on RT caused by MRI guidance include target identification, RT planning, quality assurance, treatment delivery, training, clinical workflow, tumour response assessment and treatment scheduling. In addition, entirely novel research areas that may be enabled by MRI guidance are identified for future investigation. Highlights: We present a review on the current state of MR-guided RT (RT). Speciality implications, areas for physician education and research opportunities are identified. Some impacts include target identification, quality assurance and tumour response assessment.